Strategi Promosi Melalui Media Sosial Pada Myrubylicious Fashion Store - Widuri, Andi Fika; Dewi, Catur Kumala (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
This study aims to describe the promotion strategy through social media used by one of the local fashion companies in the city of Bandung, namely the myrubylicious fashion store. The research method used is descriptive qualitative with data collection techniques through open interviews and documentation. The results of data collection are then analyzed using three stages, namely reduced data, data presented, then concluded. The results showed that myrubylicious uses a promotional mix technique consisting of 5 aspects, namely advertising, personal selling, direct marketing, public relations, and sales promotion. These five aspects are used by myrubylicious as a tool to maximize the company's promotion strategy with the goal of increasing the company's profit. This form of promotional strategy can make myrubylicious continue to survive during the onslaught of the fashion business is increasingly rampant.